Energy consumption reduction of a center-pivot with the use of a variable-frequency drive - Almeida, Isabela Alvarenga; Colombo, Alberto; Araújo, Ana Cláudia Sátiro; Almeida, Rafael Alvarenga; Costa, Jéfferson de Oliveira; Quiloango-Chimarro, Carlos Alberto (Revista Brasileira de Engenharia de Biossistemas, 2022)
Pressure demand of a center-pivot can be controlled by variable frequency drives during irrigation system operations, leading to a rational use of electrical energy. However, numerous studies encountered problems due to the lack of field data to perform the simulations. The objective of this study was to simulate the reduction of the average value of the active electrical power required to drive the pumping unit of a center-pivot irrigation system by controlling the rotational speed through a frequency inverter. The simulation was conducted considering a complete rotation of the lateral line of a central pivot, installed in an area of 70-ha, in the municipality of Formiga-MG. The simulation demonstrated the possibility of reducing the active electrical power required for the pivot pump by 18%, from an average of 131 to 107 kW. For 1300 pumping hours per year, the investment’s payback time would be two and four years for the highest (R 0.48 kWh-1) and lowest energy cost (R 0.32 kWh-1), respectively. Results suggest that irrigated areas by center-pivot with variations of topographic altitude require technical-economic evaluations for using frequency inverters.